Financial inclusion and knowledge diffusion for green growth in Sub-Saharan African countries - Arsene, Mba Fokwa (Asian Journal of Empirical Research, 2024)
This article examines the associated and interactive effects of financial inclusion measured through financial inclusion index and knowledge diffusion, measured through research and development (R&D), internet usage, and education, on green growth measured by CO2 emissions intensity due to production, in Sub-Saharan Africa. Based on a sample of 36 countries and data spanning the period from 2004 to 2018, the analysis employs POLS, Newey & West, and Driscoll & Kraay estimation methods. The findings reveal that financial inclusion, R&D, and internet usage exacerbate CO2 emissions intensity from production, thereby hindering green growth. Conversely, education plays a positive role by reducing production-related CO2 emissions and promoting sustainable practices. Education improves green growth, yet knowledge production through R&D deteriorates green growth when interacting with financial inclusion. Similarly, internet usage, when it interacts with financial inclusion, harms green growth. These results indicate that financial inclusion, R&D, and internet usage negatively impact green growth by increasing CO2 intensity related to production. The study recommends better alignment to green financial inclusion, sustainable R&D, and digital policies with environmental sustainability objectives while advocating for the promotion of environmental education to support green growth. To maximize sustainable development benefits, Sub-Saharan African countries need to adjust their development strategies by incorporating greener practices into financial inclusion, R&D, and digital technologies.